A latent class analysis of patterns of tobacco and cannabis use in Australia and their health‐related correlates. (13th February 2023) - Lim, Carmen C. W.; Leung, Janni K. Y.; Gravely, Shannon; Gartner, Coral; Sun, Tianze; Chiu, Vivian; Chung, Jack Y. C.; Stjepanović, Daniel; Connor, Jason; Scheurer, Roman W.; Hall, Wayne; Chan, Gary C. K.
Abstract: Introduction: The shifting landscape in Australia's tobacco and cannabis policies and emerging new products and modes of administration may increase experimentation and the risks of addiction to these drugs. Methods: We analysed cross‐sectional data from the 2019 National Drug Strategy and Household Survey ( n = 22, 015) of Australians aged 14 and above. Latent class analysis was used to identify distinct groups based on types of tobacco and cannabis products used. The socio‐demographic, health‐rated correlates and past‐year substance use of each latent class was examined. Results: A four‐class solution was identified: co‐use of tobacco and cannabis (2.4%), cannabis‐only (5.5%), tobacco‐only (8.0%) and non‐user (84.0%). Males (odds ratio [OR] range 1.5–2.9), younger age (OR range 2.4–8.4), moderate to high psychological distress (OR range 1.3–3.0), using illicit substances in the last year (OR range 1.41–22.87) and high risk of alcohol use disorder (OR range 2.0–21.7) were more likely to be in the tobacco/cannabis use classes than non‐users. Within the co‐use class, 78.4% mixed tobacco with cannabis and 89.4% had used alcohol with cannabis at least once. Discussion and Conclusions: Approximately 16% of respondents used tobacco or cannabis, or both substances, and no major distinct subgroups were identified by the use of different product types. Mental health issues and the poly‐substance use were more common in the class who were co‐users of cannabis and tobacco. Existing policies need to minimise cannabis and tobacco‐related harms to reduce the societal burden associated with both substances.